New isoreticular phosphonate MOFs based on a tetratopic linker. Issue 38 (13th September 2021) - Steinke, Felix; Javed, Ali; Wöhlbrandt, Stephan; Tiemann, Michael; Stock, Norbert
Abstract : The reaction of Al 3+, Ga 3+ and Fe 3+ salts with the linker H8 TPPE led to three new isoreticular compounds, structurally characterized from powder X-ray diffraction data, that exhibit different H2 O-sorption, thermal and proton conductivity properties. Abstract : The tetratopic linker 1, 1, 2, 2-tetrakis(4-phosphonophenyl)ethylene (H8 TPPE) was used to synthesize the three new porous metal–organic frameworks of composition [M2 (H2 O)2 (H2 TPPE)]· x H2 O (M = Al 3+, Ga 3+, Fe 3+ ), denoted as M-CAU-53 under hydrothermal reaction conditions, using the corresponding metal nitrates as starting materials. The crystal structures of the compounds were determined ab initio from powder X-ray diffraction data, revealing small structural differences. Proton conductivity measurements were carried out, indicating different conductivity mechanisms. The differences in proton conductivity could be linked to the individual structures. In addition, a thorough characterization via thermogravimetry, elemental analysis, IR-spectroscopy as well as N2 - and H2 O-sorption is given.